(untitled) (Acta Scientiarum. Agronomy, 2023)
The aim of the study was to assess the effect of plant regulators (gibberellic acid and naphthalene acetic acid) and adjuvant LI 700® with and without hand pollination on the fruiting and quality of Annona squamosa L. cultivars. The experiment was conducted in the experimental orchard of the Florida Tropical Research and Education Center (TREC/UF) in Homestead, Florida, USA. The experimental design in random blocks comprised 14 treatments, 10 repetitions and 3 flowers per treatment and per tree for ‘Red’ and ‘Lessard Thai’ cultivars. To assess quality, 9 fruit from each treatment were used, with 3 repetitions and 3 fruit per repetition. High instability was observed in fruit fixation rates between cultivars. The application of growth regulators did not increase fruit fixation in the tested cultivars. The application of naphthalene acetic acid had a deleterious effect on the flowers of the sugar apple cultivars. The most uneven (asymmetrical) fruit was obtained in the treatments with the application of growth regulators. The application of the adjuvant showed toxicity, causing damage to the skin of the fruit. The fruit with the greatest symmetry had the lowest levels of soluble solids and the highest toxicity. The application of growth regulators associated with hand pollination was not efficient, presenting a low percentage of fruit fixation for Annonaceae cultivars. None of the studied treatments produced parthenocarpic fruit (without seeds). The utilization of an adjuvant in the applied concentration caused damage to the fruit peels (darkening) due to toxicity in both cultivars.